Review of Kelley Nikondeha, Defiant: What the Women of Exodus Teach us About Freedom - Patricia Sharbaugh (Journal of Moral Theology)
Review of Kelley Nikondeha, _Defiant: What the Women of Exodus Teach us About Freedom_